Permetaan Zonasi Indeks Kerentanan Seismik pada Daerah Tambang CV. Bara Mitra Kencana, Kecamatan Talawi, Sawahlunto - Lady Ayu Sapitri; Adree Octova (Journals Mining Engineering : Bina Tambang, 2021)
Abstract CV. Bara Mitra Kencana is a company engaged in coal mining, the existence of mining pits changes intact rock into rock mass and the continuity of its strength is disrupted, many weak areas in the mining area are one of the factors for landslides on the mine slopes, and a cause of work accidents.To find out whether the area has a weak field or not, a zoning mapping study can be done by looking for a seismic vulnerability index using the HVSR (Harizontal to Vertical Spectral Ratio) method.The dominant frequency value is 0.615 Hz – 13,112 Hz. The amplification value in the CV Bara Mitra Kencana mining area is 1,558 – 4,417. Seismic vulnerability index 0.233 x 10-6 s6/cm – 31.723 x 10-6 s2/cm with low to high categories.Mapping of seismic susceptibility index zoning at BMK 1 point where there is a high value of 31.72 x 10-6s2/cm, BMK 2 point where the value obtained is low at 0.23 x 10-6s2/cm, BMK 5, BMK 9, BMK 10 also classified as vulnerable to damage, because the seismic vulnerability index value is also high, ranging from 11 x 10-6s2/cm – 13 x 10-6s2/cm, Point BMK 3, BMK 4, BMK 6, BMK 7, BMK 8, BMK 11, BMK 12 is relatively safe because the seismic vulnerability index value is 0.26 x 10-6s2/cm – 8.8 x 10-6s2/cm, Areas prone to damage have a high seismic vulnerability index value, high amplification value and low dominant frequency value Keywords: Maps, Vibration, Waves, and Seismic